Rates of osteoradionecrosis in resected oral cavity cancer reconstructed with free tissue transfer in the intensity‐modulated radiotherapy era. Issue 4 (20th February 2023) - Wu, Shannon S.; Hong, Hanna; Fritz, Michael; Ku, Jamie; Prendes, Brandon; Silver, Natalie; Genther, Dane J.; Ciolek, Peter; Byrne, Patrick; Brauer, Philip; Reddy, Chandana A.; Woody, Neil; et al.
Abstract: Background: Resected oral cavity carcinoma defects are often reconstructed with osteocutaneous or soft‐tissue free flaps, but risk of osteoradionecrosis (ORN) is unknown. Methods: This retrospective study included oral cavity carcinoma treated with free‐tissue reconstruction and postoperative IMRT between 2000 and 2019. Risk‐regression assessed risk factors for grade ≥2 ORN. Results: One hundred fifty‐five patients (51% male, 28% current smokers, mean age 62 ± 11 years) were included. Median follow‐up was 32.6 months (range, 1.0–190.6). Thirty‐eight (25%) patients had fibular free flap for mandibular reconstruction, whereas 117 (76%) had soft‐tissue reconstruction. Grade ≥2 ORN occurred in 14 (9.0%) patients, at a median 9.8 months (range, 2.4–61.5) after IMRT. Post‐radiation teeth extraction was significantly associated with ORN. One‐year and 10‐year ORN rates were 5.2% and 10%, respectively. Conclusions: ORN risk was comparable between osteocutaneous and soft‐tissue reconstruction for resected oral cavity carcinoma. Osteocutaneous flaps can be safely performed with no excess concern for mandibular ORN.